Capacity building of teachers to conduct fair online assessments - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Indian Journal of Anaesthesia, 2024)
Online assessments in medical education have brought about a huge transformation in the way medical students are assessed to date. As teachers will be the ones who will be working in the background in the planning, implementation, and integration process of online assessments into the medical curriculum, we must ascertain their readiness regarding the same. The best approach to get an in-depth understanding is through the conduct of a comprehensive needs assessment. As we all are aware that the successful conduct of online assessments will be defined by the competence levels of teachers, we must do capacity-building activities to empower them for their new role. We must realize that the training program may differ from one institution to another depending on the findings of the needs assessment, the available infrastructure in the institute, and the domain we are targeting in online assessments. In conclusion, online assessments have been linked with multiple benefits to all the concerned stakeholders. However, its successful planning and conduct will depend on the capacity-building training programs to augment the competence levels of teachers and their empowerment in the due course.